O direito à educação infantil e a discricionariedade administrativa - Almeida, Marcos Neri de (2008)
This current master degree dissertation aims at showing that childhood education, fundamental children's right, is a State's obligation, who does not have the faculty to refrain from offering it under any circunstancies, chiefly for children, that has absolute priority on caring their demands due to the respect to person's condition in development proccess, as well as in virtue of indisponibility that regards their rights. Childhood education is a subjective public right to children and it has its foundations even in Federal Constitution as in Child and Teenage Status, that are the main diplomas that treat this autonomous Law subject from where we outlined and identified the two fundamental principles: the absolute priority and the respect to the person condition in development proccess. Meanwhile, although the Federal Constitution have already been promulgated 19 years before, thousands of children still do not attend daycare or preschools in virtue of not enough vacancies, as on the city of São Paulo, where the lack is of, approximately, 90 thousand vacancies. With the evolution of concept of administrative discretionarity, it is up to the Judicial Power to effective this right to childhood education when it is not voluntarily by Public Administration